Electronic payment systems with fair on-line verification - BAO, Feng (Institutional Knowledge at Singapore Management University, 2000)
Electronic payment systems have been intensively studied in recent years. Generally speaking, e-payment systems can be classified into two categories, i.e., the systems with on-line verification and the systems with off-line verification. The former establishes security under the principle of prevention-before-the-fact while the latter’s security is based on the principle of detection-after-the fact. On-line systems are less risky, thus more likely to be adopted by the business community. A critical issue for on-line systems is how to make a transaction fair to each transacting party such that neither party can gain advantages over the other party in a transaction. This can be addressed with a fundamental technique of fair on-line verification. In this paper, we propose a solution to fair on-line verification for electronic payment systems, in which the customer gives verifiable encryption (by a TTP’s public key) of the digital money to the shop for on-line verification, instead of giving shop the money itself. The paper not only shows the principle of applying verifiable encryption to e-payment systems, but also focuses on building up a concrete payment system.